Assessment of Pollution Load And Its Ecological and Societal Impacts Along the Ona River, Ibadan, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study investigates the impact of pollution load on the aquatic ecosystem of the Ona River in southwestern Nigeria, as well as the associated risks to the surrounding riverine communities. The Ona River, a vital freshwater resource traversing densely populated and industrialised zones, receives diverse effluents from industrial, agricultural, and domestic activities. A stratified sampling strategy was employed across nine sites, with water samples analysed for physicochemical and microbiological parameters, including heavy metals. The Pollution Load Index (PLI) was used to quantify the levels of contamination. Results revealed significant concentrations of heavy metals, notably lead (0.008–0.028 mg/L), iron (0.115–0.396 mg/L), arsenic (0.04 ± 0.02 mg/L), and chromium (0.06 ± 0.03 mg/L), several of which exceeded World Health Organisation (WHO) permissible limits. These contaminants pose substantial ecological risks by threatening aquatic biodiversity and disrupting ecosystem services, while also presenting severe public health concerns such as neurotoxicity, carcinogenesis, and organ dysfunction. Statistical analysis indicated uniform distribution of pollutants across sites, suggesting persistent pollution sources. The findings underscore the urgent need for regular monitoring, stringent pollution control, and targeted remediation strategies, including phytoremediation and the use of constructed wetlands. This research contributes to sustainable river management by providing empirical evidence to inform policy interventions that safeguard both ecological integrity and human health.